Noise and odors pollution assessment in the bus terminal Norte - Naranjal del Metropolitano - Valverde, Jhonny (2017)
The noise and odor pollution at the Metropolitan Terminal Norte-Naranjal Bus-Station has increased due to the large number of sources that generate pollution. These fixed, mobile area sources generate a lot of noise in the morning rather than in the afternoon and evening. To evaluate the noise pollution, the sound level meter was used to measure sound pressure levels and decibels at the Metropolitan Naranjal Bus-Station. In addition, a questionnaire was developed to assess whether people's perception indicates that there is odor contamination. The results obtained indicate that noise measured at 70 dB and the case of pollution caused by the burning of solid waste (43.33%) and mobile sources (33.67%).